THE EFFECT OF WORK MOTIVATION AND DISCIPLINE ON EMPLOYEE PERFORMANCE IN HUMAN RESOURCES DEVELOPMENT AGENCY, WEST SUMATERA WITH EDUCATION AND TRAINING AS VARIABLE INTERVENING - Zukriah, Ammil; Heryanto, Heryanto (Archives of Business Research, 2019)
This study aims to examine the effect of Work Motivation and Work Discipline on Employee Performance at the Human Resources Development Agency of the Province of West Sumatra with Education and Training as an Intervening Variable. As for the population and sample in this study are all employees of the Human Resources Development Agency of West Sumatra Province, amounting to 84 employees. Based on the partial effect of work motivation on education and training 4,785 with sign. 0,000, the partial effect of work discipline on education and training is 5,000 with a sign. 0,000, the partial effect of education and training on performance is 5,380 with a sign. 0,000, Partial influence between work ethic and performance is 6.030 with sign. 0,000, Partial influence between work discipline and performance is 5,820 with sign. 0,000. For Test F obtained F count> F table or 21,453> 3,11 with a significance level of 0,000 or α 0,005. It means that there is a significant linear relationship between Work Motivation Variables (X1) and Work Discipline (X2) with Performance Variables (Y) through Education and Training Variables (I). Furthermore, F count> F table or 24.147> 3.96 with a significance level of 0,000 or α 0,005. It means that there is a significant linear relationship between Work Motivation Variables (X1) and Performance Variables (Y) through Education and Training Variables (I). And F count> F table or 24.147> 3.96 with a significance level of 0,000 or α 0,005. It means that there is a significant linear relationship between Work Discipline Variables (X2) and Performance Variables (Y) through Education and Training Variables (I). the coefficient of determination (R Square) of 0.446 is equal to 44.6%. This means that work ethic, work discipline and education and training have an effect on performance by 44.6%. While the rest (100% - 44.6% = 55.4%) is influenced by other variables outside of this regression model.